STRATEGI GURU DALAM MENCIPTAKAN PEMBELAJARAN MENYENANGKAN (FUN LEARNING) PADA PEMBELAJARAN PENDIDIKAN AGAMA ISLAM - Relly Maulita; Ismail Sukardi; Mardiah Astuti (PAI RAFAH, 2023)
Based on the results of observations made by the author at SMA Negeri 5 OKU on June 20, 2022, namely as follows in the teaching and learning process the teacher in learning Islamic Religious Education looks able to create enjoyable learning. Marked by students learning in comfortable conditions such as students having a close relationship with the teacher and all their friends, students are active in learning activities such as asking and answering various questions, doing assignments, and discussing, also when going to break time or going home from school there are no students whining to immediately break or go home. This type of research is field research with a qualitative approach. Data collection techniques using observation, interviews, and documentation.Based on the results of the study, it can be concluded that: 1) The background and purpose of implementing fun learning in Islamic Religious Education learning at SMA Negeri 5 OKU is to avoid boredom, saturation and train students to be more active. 2) The teacher's strategic steps in implementing fun learning in Islamic Religious Education learning at SMA Negeri 5 OKU are by greeting students in a friendly, enthusiastic manner, motivating students and using varied methods. 3) Supporting and inhibiting factors for teachers' strategies in creating fun learning in Islamic religious education learning at SMA Negeri 5 OKU. Supporting factors are the teacher's ability to teach and adequate facilities. The inhibiting factor is the readiness of students in participating in learning and passive students.